Analysis of Adaptive Governance in the Relocation Policy of Street Vendor Arrangement at Talang Banjar Market, Jambi City - Aulia, Ananta; Darminto, Citra (LPPM Universitas Jambi, 2026)
This research aims to explain adaptive governance in developing the capacity of the city government related to the relocation of street vendors (PKL) arrangement in the Talang Banjar market, Jambi City. The method used is qualitative with a case study approach. The results showed that the Jambi City Government, in solving the problem of relocation of street vendors arrangements in the Talang Banjar market, had not implemented adaptive governance optimally. On the indicators of polycentric and multi-layered institutions, it was found that the Jambi city government had formed an integrated team. Still, it had not run optimally, so the settlement had not occurred. Furthermore, the indicators of collaboration and participation are still not optimal among fellow institutions because there are still egocentric institutions in collaboration. Meanwhile, in the indicators of self-organization and networking, the government has formed a merchant association to organize the market. However, the organization is no longer active, and its members are decreasing. Meanwhile, on the indicators of learning and innovation in structuring street vendors, the Jambi City government has conducted program evaluations, but there has been no sustainable innovation for the problem of relocating street vendors in the Talang Banjar market in Jambi City. This research enriches the literature on adaptive governance by demonstrating that the success of implementation is not only determined by the existence of institutional structures such as integrated teams or trade associations, but also by the effectiveness of functions and interactions among the actors within them